On Simultaneous Weakly-Chebyshev Subspaces (Analysis in Theory and Applications, 2011)
In this paper, we shall introduce and characterize simultaneous quasi-Chebyshev (and weakly-Chebyshev) subspaces of normed spaces with respect to a bounded set $S$ by using elements of the dual space.
Keywords: dual space; best simultaneous approximation; simultaneous quasi-Chebyshev subspace; simultaneous weakly-Chebyshev subspace.